The Influence of Smartphones on Adolescent Sleep: A Systematic Literature Review - Sofia de Sá; Ana Baião; Helena Marques; Maria do Céu Marques; Maria José Reis; Sandra Dias; Marta Catarino (MDPI AG, 2023)
(1) Background: Sleep is considered to be a complex condition for human beings, with the aim of ensuring physical and psychological recovery. Technology, including the cell phone, is a tool for teenagers that ensures they are always available to interact, even at night. This study aims to understand the influence of the use of smartphones on adolescent sleep quality. (2) Methods: The guidelines proposed by the Joanna Briggs Institute were followed. The search was conducted in October 2022 through the EBSCOhost platform, with access to the CINAHL Complete and Medline databases and through the b-On database. (3) Results: The use of electronic equipment plays an important role in adolescents' lives. There is a negative relationship between the use of electronic equipment, such as smartphones, and sleep, for reducing both the quality and quantity of sleep. There is also a relationship between nighttime smartphone use, insufficient sleep, and mental health problems. (4) Conclusions: The use of new technologies at night causes a change in the behavior of adolescents with repercussions in terms of the quality of sleep and sleep duration and consequent well-being and performance during the day.